PASE: a novel method for functional prediction of amino acid substitutions based on physicochemical properties - Li, Xidan; Kierczak, Marcin; Shen, Xia; ahsan, muhammad; Carlborg, Örjan; Marklund, Stefan (Frontiers in Genetics, 2013)
Abstract Background: Non-synonymous single nucleotide polymorphisms within the coding regions of genes causing amino acid substitutions may have a large impact on protein function. The possibilities to identify non-synonymous single nucleotide polymorphisms across genomes have increased notably with the advent of next-generation sequencing technologies. Thus, there is a strong need for efficient bioinformatics tools to predict the functional effect of amino acid substitutions. Such tools can be used to identify the most promising candidate mutations for further experimental validation. Results: Here we present PASE, a novel method that predicts the effect of an amino acid substitutions based on physicochemical property changes. Evaluation of PASE, using a few amino acid substitutions of known phenotypic effects and 3338 human amino acid substitutions, for which functional effects have previously been scored with the widely used SIFT and PolyPhen tools, show that PASE is a useful method for functional prediction of amino acid substitutions. We also show that the predictions can be further improved by combining PASE with information about evolutionary conservation. Conclusion: PASE is a novel algorithm for predicting functional effects of amino acid substitutions, which can be used for pinpointing the most interesting candidate mutations. PASE predictions are based on changes in seven physicochemical properties and can improve predictions from many other available tools which are based on evolutionary conservation. Using available experimental data and predictions from the already existing tools, we demonstrate that PASE is a useful method for predicting functional effects of amino acid substitutions, even when a limited number of query sequence homologs/orthologs are available.